PENGAWASAN DAN KOORDINASI KERJA SERTA PENGARUHNYA TERHADAP PRODUKTIVITAS KERJA KARYAWAN - Arif Rahman Putra (Universitas Islam Balitar, 2017)
Human resources are an asset for the organization to achieve its goals and this means that the organization needs qualified human resources to run its perasional. To achieve this, organizations need to monitor and coordinate work. The result of supervision and work coordination is expected to give effect to work productivity. The purpose of this research is (1) to know and analyze the partial influence of supervision and work coordination on work productivity; (2) to know and analyze the effect simultaneously supervision and coordination of work on employee work productivity; and (3) to know and analyze which is more dominant among supervision and work coordination to work productivity of employees. The research was conducted in one of the largest factories in sidoarjo city with 10000 employees. Samples were taken as many as 200 people with random technique. The data is done by using SPSS program with multiple regression analysis method. The results of the research are (1) supervision and coordination of work have a significant effect partially on work productivity; (2) supervision and coordination of work have significant effect simultaneously on work productivity; (3) work supervision proved to have a significant dominant influence on work productivity.